Chemical, thermophysical, rheological, and microscopic characterisation of rubber modified asphalt binder exposed to UV radiation. (14th September 2020) - Zadshir, Mehdi; Ploger, Desiree; Yu, Xiaokong; Sangiorgi, Cesare; Yin, Huiming
Abstract : In this work, the effect of ultraviolet (UV) radiation on samples of asphalt binder mixed with crumb rubber is studied. Two sets of samples are characterised using a PG 64-22 neat binder with different percentages of rubber particles being 0, 16.6, and 20.0 wt.%. One set of the samples was stored at ambient temperature (called the unaged set) and the other was inserted inside an accelerated weathering tester for 100 h (called the UV-aged set). Thermal conductivity, chemical indices, rheology, and morphology of both sets of samples are tested using the flash method, differential scanning calorimeter (DSC), Fourier-Transform Infrared Spectroscopy (FTIR), dynamic shear rheometer (DSR), and Scanning Electron Microscope (SEM), respectively. Results show that the addition of rubber leads to a reduction of specific heat for the rubber-modified binders. Specific heat capacities of the three UV aged samples are larger than those of their unaged counterparts, and the 16.6%-aged has the highest value. FTIR spectra of the three unaged samples are very similar, whereas distinct changes occur after UV exposure. The normalised absorbance of the peak associated with S = O group increases and the peak for the aliphatic group decreases after UV aging, showing some evidence of oxidation due to UV aging. Use of crumb rubber in the binder decreases the thermal conductivity and 20.0 wt.% sample is even less conductive compared to the 16.6 wt.%. At all temperatures above 25°C, aged samples have lower thermal conductivity than the unaged ones, except neat binder which is opposite. Rheological measurements show that the complex modulus of the samples increases with the addition of rubber particles and also after aging. However, 16.6% rubber-modified sample shows the least increase in modulus after aging. Microscopic morphology shows that UV radiation causes cracks in both neat and rubber modified binder. Smaller cracks are seen to form, and the cracked pieces are stuck together in the rubber modified binders, whereas less cohesion between the cracks is observed in the neat binder.